Variability of Catharanthus roseus based on morphological and anatomical characters, and chlorophyll contents - siti samiyarsih; NETTYANI NAIPOSPOS; DIAN PALUPI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Samiyarsih S, Naipospos N, Palupi D. 2019. Variability of Catharanthus roseus based on morphological and anatomical characters, and chlorophyll contents. Biodiversitas 20: 2986-2993. Catharanthus roseus (L.) is an important medicinal plant of the family Apocynaceae used to treat many of the diseases. C. roseus also possess good antioxidant potential. The purpose of this research was 1) to determine the variability of C. roseus based on the morphological, anatomical characters and chlorophyll contents, 2) to know the differences in morphological, anatomical characteristics and chlorophyll contents of C. roseus found in Banyumas Regency. The research used a survey method, with a purposive sampling technique. Preparation of leaf for anatomical analysis was based on paraffin method. The results showed that C. roseus in Banyumas Regency were grouped into eight varieties. The morphological characters observed consisted of 21 characters, 8 quantitative characters, and 13 qualitative characters. Most of the quantitative morphological and anatomical characters were significantly diverse (p <0.05) except for petiole length, corolla number, stomata width and number of trichomata. The eight varieties of C. roseus have different chlorophyll a, chlorophyll b, and total chlorophyll contents but their anthocyanin contents were not significantly different.